A Novel AC/DC Power Flow: HVDC-LCC/VSC Inclusion Into the PFPD Bus Admittance Matrix - Roberto Benato; Giovanni Gardan (IEEE Access, 2022)
In this paper, the matrix algorithm PFPD is generalized in order to compute the power flow solution of real and large AC/DC transmission networks. In particular, it is demonstrated that the HVDC-VSC/LCC links can be seen from the AC power systems as PV/PQ constraints, which englobe both the AC and DC characteristics of the HVDC links. The proposed analytical formulation to assess the PV/PQ constraints is valid for any other numerical methods (e.g., Newton-Raphson and derived, Gauss-Seidel, etc.). Furthermore, an iterative procedure for estimating the reactive power absorption of HVDC-LCC links from the power system is proposed. In order to validate the algorithm, solution comparisons with the commercial software DIgSILENT PowerFactoy are presented. This validation procedure shows that the algorithm can analyse large and real HVAC/HVDC networks (e.g., the Italian transmission one with its five HVDC links). Therefore, the conciseness, accuracy and performances of PFPD for studying real and large AC/DC power systems is confirmed.